The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1471-2458-11-727
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of sexually transmitted diseases (STDs) among school-going adolescents in Europe: a systematic review of published literature

Abstract: BackgroundSexually transmitted diseases (STDs) are a major health problem affecting mostly young people, not only in developing, but also in developed countries.We conducted this systematic review to determine awareness and knowledge of school-going male and female adolescents in Europe of STDs and if possible, how they perceive their own risk of contracting an STD. Results of this review can help point out areas where STD risk communication for adolescents needs to be improved.MethodsUsing various combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
125
2
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 35 publications
18
125
2
10
Order By: Relevance
“…However, the majority of students did not know the early symptoms, which could delay their seeking proper treatment. The level of knowledge among the students in this study is much lower than the levels reported from European adolescents in 1988 [20] (13% vs. 56%, correct answers for the same questions). The majority of students in this study exhibited appropriate health-seeking behavior, whereas a small percentage of infected students who would keep silent could be putting themselves and their partners at risk by delaying or refusing proper treatment.…”
Section: Deficient Knowledge In Sticontrasting
confidence: 45%
See 1 more Smart Citation
“…However, the majority of students did not know the early symptoms, which could delay their seeking proper treatment. The level of knowledge among the students in this study is much lower than the levels reported from European adolescents in 1988 [20] (13% vs. 56%, correct answers for the same questions). The majority of students in this study exhibited appropriate health-seeking behavior, whereas a small percentage of infected students who would keep silent could be putting themselves and their partners at risk by delaying or refusing proper treatment.…”
Section: Deficient Knowledge In Sticontrasting
confidence: 45%
“…It has been reported that adolescents in Europe have low levels of knowledge and awareness of STIs, with the exception of HIV/AIDS [20]. Likewise in this study, there exist considerable deficiencies in students' knowledge about STI symptoms, complications, transmissions, and preventive methods.…”
Section: Deficient Knowledge In Stimentioning
confidence: 50%
“…A paper-based survey was administered to students (grades 10-12 [aged [16][17][18][19][20][21] years]) during sexual-health teaching sessions. Students attending these classes were selected for the present analysis because they were felt to be of the most culturally and ethically acceptable age to administer a survey related to sexual-health behaviors and STIs.…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge is the first step of protecting people from the diseases and an adequate and proper knowledge about STDs may be an appropriate preventive measure. Several studies at the global level show that age, sex, ethnicity, place of residence and parental education are significantly related to the knowledge of STDs among youths (Stone, Ingham & Simkhada, 2003, MOPH;New ERA and IFC International, 2012;Upreti, Regmi, Pant & Simkhada, 2009;Samkange-Zeeb, Spallek & Zeeb, 2011). Although a large number of cross sectional KAP studies on STDs including HIV/AIDS has been conducted in the context of Nepal by taking sample for the specific areas, none of the studies are based on the nationally representative sample.…”
Section: Introductionmentioning
confidence: 99%